Amputation: Evaluation and Treatment. (5th September 2018) - Gordon, Wade; Balsamo, Luke; Talbot, Max; Osier, Charles; Johnson, Anthony; Shero, John; Potter, Benjamin; Stockinger, Zsolt T
Abstract: Combat extremity injury and amputation is a life threatening injury. Initial surgical care should focus on hemostasis followed by irrigation and debridement of contaminated and nonviable tissue. Preservation of limb length begins at the initial surgical procedure, to include retention of atypical soft tissue flaps for later reconstruction and treatment of proximal fractures. Serial irrigation and debridements are required throughout the MEDEVAC system as the evolving zone of injury becomes more mature, followed by the appropriate timing of closure outside the combat theater.